Keefektifan pendidikan anti-bullying terhadap pengetahuan, sikap, dan self-efficacy pada guru di Yogyakarta - Bayu Seto Rindi Atmojo; Imam Permana (STIKes Surya Global Yogyakarta, 2020)
Cases of bullying in schools have become a widespread phenomenon and have a negative impact on the school atmosphere. A good and fearless learning environment needs attention. Educational institutions have the task of creating and guaranteeing a conducive and safe learning atmosphere so that students feel happy and comfortable while at school. This can be supported by teachers who have good knowledge, attitudes and self-efficacy towards bullying cases. This study aims to determine the effectiveness of anti-bullying education on teacher's knowledge, attitudes, and self-efficacy. The method used in this study uses a pre-experimental quantitative approach with a one-group pretest-posttest design. The population in this study were all teachers of SMP 11 Yogyakarta, the sampling technique used total sampling, so the sample was 23 teachers. Test data analysis used the Wilcoxon test. Knowledge prior to the intervention of the average respondent was given in the good category, good enough attitude and self-efficacy in the poor category. Knowledge after being given an intervention is mostly in the good category, good attitude and good self-efficacy. Wilcoxon test results on each variable of knowledge, attitude and self-efficacy obtained p value 0,002, which means that anti-bullying education affects the knowledge, attitudes and self-efficacy of teachers. It can be concluded that anti-bullying education is effective in increasing teacher’s knowledge, attitudes and self-efficacy in SMP 11 Yogyakarta